Strategi Peningkatan Produktivitas Budidaya Udang Vaname (Litopenaeus Vannamei) Di CV. Daun Prima Kabupaten Blitar, Provinsi Jawa Timur - Djoko Surahmat; Dewi Alima Nostalia; Agestia Ananda Putri Wardana (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
This study aims to identify and analyze strategies for improving the productivity of vannamei shrimp (Litopenaeus vannamei) farming at CV. Daun Prima, Blitar Regency, East Java Province. The methods used in this study include field observation, interviews with managers and farmers, as well as secondary data analysis related to shrimp farming practices at the site. The results indicate that key factors influencing productivity include water quality management, high-quality feed, and the use of appropriate technology. The recommended strategies for improving productivity include enhancing the water quality monitoring system, implementing efficient feeding techniques, and providing training for farmers on the latest farming technologies. With the implementation of these strategies, it is expected that the sustainable production of vannamei shrimp at CV. Daun Prima can be improved.